The source of the US /EU productivity gap: Less and less efective R&D - Davide Castellani; Mariacristina Piva; Torben Schubert; Marco Vivarelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
Using data on the US and EU top R&D spenders from 2004 until 2012, this paper investigates the sources of the US/EU productivity gap. We find robust evidence that US firms have a higher capacity to translate R&D into productivity gains (especially in the high-tech industries), and this contributes to explaining the higher productivity of US firms. Conversely, EU firms are more likely to achieve productivity gains through capital-embodied technological change at least in medium and low-tech sectors. Our results also show that the US/EU productivity gap has worsened during the crisis period, as the EU companies have been more affected by the economic crisis in their capacity to translate R&D investments into productivity. Based on these findings, we make a case for a learning-based and selective R&D funding, which - instead of purely aiming at stimulating higher R&D expenditures - works on improving the firms' capabilities to transform R&D into productivity gains.
Keywords: O33; O51; O52; 330; R&D; productivity; economic crisis; US; EU